Efektifitas Kinerja Karyawan Melalui Komitmen Organisasi, Komunikasi Kerja dan Keselamatan dan Kesehatan Kerja pada Saat Pandemi PT. Alfa Scorpii Medan - Yeni Ariesa; Ellen Chandra (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this research is to test the organizational commitment, work communication,and occupational safety and health of PT Alfa scorpii employee’s performance. This research using quantitative approach which is the descriptive quantitative analysis along with explanatory descriptive.The population used are 148 employees with 108 sample obtaind from simple random sampling. This hypothesis using multiple linear regression analysis.The result shown that there are partial impact and significant organizational commitment,work communication and occupational safety and health of PT Alfa Scorpii Medan employees.Simultaneously, those variabels has a positive and significant impact with the performance of PT Alfa Scorpii Medan employees with 28.1% of the adjusted R square result can be describe as the organization commitment, work communication and occupational safety and health while the rest can be explained as other variabels which are organizational culture, compensation and others.